The Effect of Government Expenditures on Indonesian Unemployment and Poverty Level - Sarah Dina (Proceedings of AICS - Social Sciences, 2017)
Government expenditures is one of fiscal policy in overcoming market failure. By the government intervention through expenditure budget is expected to create multiplier effect to other economic sectors which can increase economic growth, so that has a positive impact for unemployment and poverty. This research purpose is to see how far government expenditures influence on unemployment and poverty in Indonesia. This study uses secondary data obtained from the Central Bureau of Statistics (BPS) from 2005-2010, with econometric model, Ordinary Least Square (OLS) method. This research explain that government expenditures contribute to unemployment and poverty but central government’s role is still more dominant in reducing unemployment and poverty in Indonesia compared by local government’s role. It is suggested that central and regional governments should have a common vision and step to reduce the unemployment and poverty level.